Unique benthic foraminiferal communities (stained) in diverse environments of sub-Antarctic fjords, South Georgia - Majewski, Wojciech; Szczuciński, Witold; Gooday, Andrew J. (Copernicus Publications, 2023)
Sub-Antarctic fjords are among the environments most affected by the recent climate change. In our dynamically changing world, it is essential to monitor changes in these vulnerable settings. Here, we present a baseline study of “living” (rose-bengal-stained) benthic foraminifera from fjords of South Georgia, including fjords with and without tidewater glaciers. Their distribution is analyzed in the light of new fjord water and sediment property data, including grain size and sorting, total organic carbon, total sulfur, and δ13C of bulk organic matter. Four well-defined foraminiferal assemblages are recognized. Miliammina earlandi dominates in the most restricted, near-shore and glacier-proximal habitats, Cassidulinoides aff. parkerianus in mid-fjord areas, and Globocassidulina aff. rossensis and an assemblage dominated by Ammobaculites rostratus, Reophax subfusiformis, and Astrononion echolsi are in the outer parts of the fjords. Miliammina earlandi can tolerate strong glacial influence, including high sedimentation rates in fjord heads and sediment anoxia, as inferred from sediment color and total organic carbon  sulfur ratios. This versatile species thrives both in the food-poor inner reaches of fjords that receive mainly refractory petrogenic organic matter from glacial meltwater and in shallow-water coves, where it benefits from an abundant supply of fresh, terrestrial, and marine organic matter. A smooth-walled variant of C. aff. parkerianus, apparently endemic to South Georgia, is the calcareous rotaliid best adapted to inner-fjord conditions characterized by moderate glacial influence and sedimentation rates and showing no preference for particular sedimentary redox conditions. The outer parts of fjords with clear, well-oxygenated bottom water are inhabited by G. aff. rossensis. Ammobaculites rostratus, R. subfusiformis, and A. echolsi dominate in the deepest-water settings, with water salinities ≥ 33.9 PSU and temperatures 0.2–1.4 ∘C, characteristic of winter water and Upper Circumpolar Deep Water. The inner- and mid-fjord foraminiferal assemblages seem specific to South Georgia, although with continued warming and deglaciation, they may become more widespread in the Southern Ocean.
Keywords: Sub-Antarctic; South Georgia; fjords; foraminifera; benthic foraminifera; hydrology; sediments; marine sediments; grain size; geochemistry; living foraminifera; fjord environment; benthos; organic matter; foraminiferal assemblage; water masses; tidewater glacier; glacimarine sediments